A Validated Risk Prediction Model for Bone Fragility in Children With Acute Lymphoblastic Leukemia. (5th October 2021) - Verwaaijen, Emma J.; Ma, Jinhui; de Groot‐Kruseman, Hester A.; Pieters, Rob; van der Sluis, Inge M.; van Atteveld, Jenneke E.; Halton, Jacqueline; Fernandez, Conrad V.; Hartman, Annelies; de Jonge, Robert; Lequin, Maarten H.; te Winkel, Mariël L.; et al.
ABSTRACT: Although bone fragility may already be present at diagnosis of pediatric acute lymphoblastic leukemia (ALL), routine performance of dual‐energy X‐ray absorptiometry (DXA) in every child is not universally feasible. The aim of this study was to develop and validate a risk prediction model for low lumbar spine bone mineral density (LS BMD Z ‐score ≤ −2.0) at diagnosis, as an important indicator for fracture risk and further treatment‐related BMD aggravation. Children with ALL (4–18 years), treated according to the Dutch Childhood Oncology Group protocol (DCOG‐ALL9; model development; n  = 249) and children from the Canadian Steroid‐Associated Osteoporosis in the Pediatric Population cohort (STOPP; validation; n  = 99) were included in this study. Multivariable logistic regression analyses were used to develop the prediction model and to confirm the association of low LS BMD at diagnosis with symptomatic fractures during and shortly after cessation of ALL treatment. The area under the receiver operating characteristic curve (AUC) was used to assess model performance. The prediction model for low LS BMD at diagnosis using weight (β = −0.70) and age (β = −0.10) at diagnosis revealed an AUC of 0.71 (95% CI, 0.63–0.78) in DCOG‐ALL9 and 0.74 (95% CI, 0.63–0.84) in STOPP, and resulted in correct identification of 71% of the patients with low LS BMD. We confirmed that low LS BMD at diagnosis is associated with LS BMD at treatment cessation (OR 5.9; 95% CI, 3.2–10.9) and with symptomatic fractures (OR 1.7; 95% CI, 1.3–2.4) that occurred between diagnosis and 12 months following treatment cessation. In meta‐analysis, LS BMD at diagnosis (OR 1.6; 95% CI, 1.1–2.4) and the 6‐month cumulative glucocorticoid dose (OR 1.9; 95% CI, 1.1–3.2) were associated with fractures that occurred in the first year of treatment. In summary, a prediction model for identifying pediatric ALL patients with low LS BMD at diagnosis, as an important indicator for bone fragility, was successfully developed and validated. This can facilitate identification of future bone fragility in individual pediatric ALL patients. © 2021 American Society for Bone and Mineral Research (ASBMR).